Pengaruh Influencer Marketing, Inovasi Produk Dan Persepsi Harga Terhadap Minat Beli Konsumen Produk Jiniso (Studi Mahasiswa Kota Malang) - Izza, Nikmatul; Susyanti, Jeni; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study is to determine and analyze the effect of Influencer Marketing variables, Product Innovation and Price Perception on Purchase Interest partially and simultaneously through quantitative methods, which were carried out by distributing questionnaires in the form of Google Forms to 75 respondents. The sample in this study consisted of students from Malang City. The data analysis technique used is multiple linear regression analysis, which is processed using SPSS version 25. The results showed that both partially and simultaneously, the variables Influencer Marketing, Product Innovation and price perception have a significant relationship to purchase intention.  Keywords: Influencer Marketing, Product Innovation, Price Perception, Interset